A Conversation with Sally McCallum. Issue 5 (18th August 2018) - McCallum, Sally; Willer, Mirna
Abstract: In this conversation, conducted during the IFLA conference in Wrocław, Poland in August 2017, Sally McCallum retells her beginnings at the Library of Congress in Washington D.C. when she worked with Henriette Avram and Lucia Rather on the development of the MARC and UNIMARC formats. Other topics include conversion between MARC and UNIMARC, MARC21 and BIBFRAME projects, and her views on: RDA (Resource Description and Access); ISBD (International Standard Bibliographic Description); IFLA LRM (IFLA Library Reference Model); and UBC (Universal Bibliographic Control) in the face of technological changes.